Voluntary Genital Ablations: Contrasting the Cutters and Their Clients. Issue 3 (17th July 2014) - Jackowich, Robyn A.; Vale, Rachel; Vale, Kayla; Wassersug, Richard J.; Johnson, Thomas W.
Abstract Introduction Some healthy males voluntarily seek castration without a recognized medical need. There are currently no standards of care for these individuals, which cause many of them to obtain surgery outside of a licensed medical setting. We seek to understand who performs these surgeries. Aim This study aims to characterize individuals who perform or assist in genital ablations outside of the healthcare system. Methods A cross‐sectional Internet survey posted on eunuch.org received 2, 871 responses. We identified individuals who had performed or assisted in human castrations ("cutters"; n = 98) and compared this group with all other survey respondents (n = 2, 773), who had not assisted in castrations. Next we compared the cutters with the voluntary eunuchs. Lastly, because many of the cutters have themselves been castrated, we also divided the physically castrated population (n = 278) into cutters (n = 44) and noncutters (n = 234) and compared them. Main Outcome Measures Self‐reported questionnaires were used to collect demographic information, gender identity and presentation, selected childhood experiences, and history of aggressive behaviors, self‐harming behaviors, and hospitalization. Results Distinguishing characteristics of cutters included: (i) presenting themselves as very masculine, (ii) having had their longest sexual relationship with a man, (iii) growing up on a farm, (iv) witnessing animal castrations, (v) having a history of sexually inappropriate behavior, (vi) having been threatened with genital mutilation as a child, (vii) having a history of self‐harm, (viii) being raised in a devoutly Christian household, (ix) having had an underground castration themselves, and (x) having body piercings and/or tattoos. Conclusions This study may help identify individuals who are at risk of performing illegal castrations. That information may help healthcare providers protect individuals with extreme castration ideations from injuring themselves or others. Jackowich RA, Vale R, Vale K, Wassersug RJ, and Johnson TW. Voluntary genital ablations: Contrasting the cutters and their clients. Sex Med 2014;2:121–132.